High-throughput mutation detection underlying adaptive evolution of Escherichia coli-K12 - Honisch, Christiane; Raghunathan, Anu; Cantor, Charles R.; Palsson, Bernhard Ø.; van den Boom, Dirk (Genome Research, 2004)
Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) analysis of base-specific cleavage products is an efficient, highly accurate tool for the detection of single base sequence variations. We describe the first application of this comparative sequencing strategy for automated high-throughput mutation detection in microbial genomes. The method was applied to identify DNA sequence changes that occurred in Escherichia coli K-12 MG1655 during laboratory adaptive evolution to new optimal growth phenotypes. Experiments were based on a genome-scale in silico model of E. coli metabolism and growth. This model computes several phenotypic functions and predicts optimal growth rates. To identify mutations underlying a 40-d adaptive laboratory evolution on glycerol, we resequenced 4.4% of the E. coli-K12 MG1655 genome in several clones picked at the end of the evolutionary process. The 1.54-Mb screen was completed in 13.5 h. This resequencing study is the largest reported by MALDI-TOF mass spectrometry to date. Ten mutations in 40 clones and three deviations from the reference sequence were detected. Mutations were predominantly found within the glycerol kinase gene. Functional characterization of the most prominent mutation shows its metabolic impact on the process of adaptive evolution. All sequence changes were independently confirmed by genotyping and Sanger-sequencing. We demonstrate that comparative sequencing by base-specific cleavage and MALDI-TOF mass spectrometry is an automated, fast, and highly accurate alternative to capillary sequencing.